A study on students' needs in learning English for pharmacy (A starting point to design innovative syllabus) - Tri Agustini Solihati; Nurti Rahayu (University of Kuningan, 2020)
This study aims to discover the needs of pharmacy students as an input to design an ESP syllabus. The needs analyses were conducted by distributing questionnaires to and interviewing the respondents. The responses were analyzed based on a comprehensive concept of need analysis proposed by Dudley-Evans and St. John. The findings showed that most students consider themselves poor in vocabulary and weak in speaking, listening, writing, and pronunciation. Hence, it is crucial to improve their skills to enable them from communicating effectively with foreign patients and avoiding misunderstanding which may happen when interacting with foreign patients. Therefore, developing an appropriate ESP syllabus for pharmacy course could be possibly developed based on these findings and the theory of material development.